Biologic therapy with anti-TNFa in spondyloarthritides and other autoimmune diseases - G. Lapadula (PAGEPress Publications, 2011)
Objective: To evaluate the efficacy of the anti-TNFa (Tumor Necrosis Factor alpha) drugs in a variety of pathologic conditions such as psoriatic arthritis, undifferentiated entheso-arthritides, chronic inflammatory bowel diseases, adult onset Still's disease, Behcet disease. Methods: Review of all published studies evaluating the efficacy of these drugs (mainly infliximab and etanercept, adalimumab to a lesser degree) on the above diseases. Results: Results are reported for each pathologic condition. Both drugs showed to be very efficacious in all the above conditions, except Crohn disease where etanercept does not seem adequate. Conclusions: Both drugs work extremely well, even though comparison between infliximab and etanercept efficacy cannot be performed, due to the lack of a direct comparison.